Tujuan dan Efikasi Diri untuk Mendongkrak Kinerja Pengajar dan Staf Sekolah Islam di Jakarta - Santi Retno Sari (LPMP Imperium, 2021)
This study aims to analyze the moderating effect of self-efficacy on the relationship between goal commitment and motivation. This is based on goal setting theory which is taken from the perspective of goal commitment interacting with self-efficacy in increasing motivation. The method used in this research is moderation testing with the help of the macroprocess v3.15 tool, the research takes a population of Islamic school teachers in Jakarta. one hundred one out of 135 is obtained from the slovin formula and taken by simple random sampling. Data processing gives the results of all hypotheses accepted. There is self-efficacy moderation in the relationship between goal commitment and motivation. Going forward, increase the motivation of teachers and education staff by providing goals that increase commitment to goals such as by participating, and increasing self-efficacy in achieving tasks so that this will lead to better work results.: goal commitment; goal setting; motivation; Self efficacy.